Zinc Supplementation Trial in Pediatric Chronic Kidney Disease: Effects on Circulating FGF-23 and Klotho - V. Belostotsky; S. A. Atkinson; G. Filler (Canadian Journal of Kidney Health and Disease, 2024)
Background: Zinc status, its role in bone metabolism and efficacy of deficiency correction has not been well studied in children with chronic kidney disease (CKD). Objectives: The primary objective was to investigate whether 3 months of oral zinc supplementation corrects zinc deficiency in children with CKD who have native or transplanted kidneys. The secondary objective was to compare circulating intact FGF-23 (iFGF-23), c-terminal FGF-23 (cFGF-23), and Klotho between zinc-sufficient and zinc-deficient children with CKD and to assess the relationship between circulating zinc, iFGF-23, cFGF-23, Klotho, bone biomarkers, copper, and phosphate excretion pre-supplementation and post-supplementation of zinc. Methods: Forty-one children (25 male and 16 female, age 12.94 ± 4.13 years) with CKD in native or transplanted kidneys were recruited through 2 pediatric nephrology divisions in Ontario, Canada. Of those, 14 patients (9 native CKD, 5 transplant CKD) with identified zinc deficiency (64% enrollment rate) received zinc citrate supplement for 3 months: 10 mg orally once (4-8 years) or twice (9-18 years) daily. Results: Zinc deficiency (plasma concentration < 11.5 µmol/L) was found in 22 patients (53.7%). A linear regression model suggested that zinc concentration reduced by 0.026 µmol/L ( P = .04) for every 1-unit of estimated glomerular filtration rate (eGFR) drop. Zinc deficiency status was associated with higher serum iFGF-23; however, this was predominantly determined by the falling GFR. Zinc deficient and sufficient children had similar circulating c-FGF-23 and alpha-Klotho. Normalization of plasma zinc concentration was achieved in 8 (5 native CKD and 3 transplant CKD) out of 14 treated patients rising from 10.04 ± 1.42 to 12.29 ± 3.77 μmol/L ( P = .0038). There were no significant changes in other biochemical measures in all treated patients. A statistically significant ( P = .0078) rise in c-FGF-23 was observed only in a subgroup of 11 children treated with zinc but not receiving calcitriol. Conclusions: Zinc status is related to kidney function and possibly connected to bone metabolism in patients with CKD. However, it plays a minor role in fine-tuning various metabolic processes. In this exploratory non-randomized study, 3 months supplementation with zinc corrected deficiency in just over half of patients and only modestly affected bone metabolism in asymptomatic CKD patients.